Inhibition of organic cation transporter 3 activity by tyrosine kinase inhibitors. (13th March 2021) - Alim, Karima; Moreau, Amélie; Bruyère, Arnaud; Jouan, Elodie; Denizot, Claire; Nies, Anne T.; Parmentier, Yannick; Fardel, Olivier
Abstract: Organic cation transporter (OCT) 3 ( SLC22A3 ) is a widely expressed drug transporter, handling notably metformin and platinum derivatives, as well as endogenous compounds like monoamine neurotransmitters. OCT3 has been shown to be inhibited by a few marketed tyrosine kinase inhibitors (TKIs). The present study was designed to determine whether additional TKIs may interact with OCT3. For this purpose, the effects of 25 TKIs toward OCT3 activity were analyzed using OCT3‐overexpressing HEK293 cells. 13/25 TKIs, each used at 10 µM, were found to behave as moderate or strong inhibitors of OCT3 activity, that is, they decreased OCT3‐mediated uptake of the fluorescent dye 4‐(4‐(dimethylamino)styryl)‐N‐methylpyridinium iodide by at least 50% or 80%, respectively. This OCT3 inhibition was correlated to some molecular descriptors of TKIs, such as the percentage of H atoms and that of cationic forms at pH = 7.4. It was concentration‐dependent, notably for brigatinib, ceritinib, and crizotinib, which exhibited low half maximal inhibitory concentration (IC50 ) values in the 28–106 nM range. Clinical concentrations of these three marketed TKIs, as well as those of pacritinib, were next predicted to inhibit in vivo OCT3 activity according to regulatory criteria. Cellular TKI accumulation experiments as well as trans ‐stimulation assays, however, demonstrated that OCT3 does not transport brigatinib, ceritinib, crizotinib, and pacritinib, thus discarding any implication of OCT3 in the pharmacokinetics of these TKIs. Taken together, these data suggest that some TKIs may act as potent inhibitors of OCT3 activity, which may have consequences in terms of drug–drug interactions and toxicity.